Poly (lactic acid) : synthesis structures, properties, processing and applications - Auras, Rafael (Wiley series on polymer engineering and technology, 2010)
This book describes the synthesis, properties, and processing methods of poly(lactic acid) (PLA), an important family of degradable plastics. As the need for environmentally-friendly packaging materials increases, consumers and companies are in search for new materials that are largely produced from renewable resources, and are recyclable